Frictional forces produced by three different ligation methods in two different types of brackets in 0.016 nickel-titanium wire: An in vitro study - B Kanagasabapathy; M M Varadharaja; R Saravanan; V Vignesh Kumar; R Mahalakshmi; Reshmi Leila Ninan; A Srivel Vigneswari; S Dwaragesh (Wolters Kluwer Medknow Publications, 2021)
Introduction: The aim of this in vitro study was to compare the frictional forces produced by three types of ligatures (conventional elastic ligatures, unconventional elastic ligatures, and tooth-colored ligature wire) on ceramic bracket and stainless steel brackets with 0.016 nickeltitanium (NiTi) archwire in the dry state. Materials and Methods: Twenty each stainless steel brackets and ceramic brackets (0.022 slot central incisor brackets) were mounted on the acrylic block. This assembly was mounted on the Instron machine with the crossheads moving upward at a speed of 10 mm/min in the upper jaw of the Instron machine, one acrylic block with hook and a straight length of 0.016 NiTi wire was attached to it. This wire was ligated to brackets with three different ligation methods. In each test, the brackets were moved a distance of 4 mm, 8 mm, and 12 mm across the central space, and the load cell readings were recorded on the digital display. The difference between the readings is noted. Results: Stainless steel brackets with 0.016 NiTi archwire ligated with conventional, unconventional, and tooth-colored ligation with the movement of 4 mm, 8 mm, and 12 mm shows that the tooth-colored ligation indicating least frictional force decay. Comparison of frictional forces (in newtons) between ceramic brackets and stainless steel brackets using 0.016 NiTi wire for a movement of 12 mm shows that stainless steel bracket with tooth-colored ligation produced least frictional force compared with ceramic bracket. Conclusion: Based on this study results, we can conclude that stainless steel brackets produce less frictional force compared to ceramic brackets. Similarly, tooth-colored ligatures can be preferred to reduce friction during leveling stage.